Early growth of camu-camu plants with nitrogen fertilization through fertirrigation - Abanto-Rodríguez, Carlos (2016)
The objective of this study was to evaluate the effect of different doses of nitrogen (N), applied via fertirrigation, on the initial growth components of the camu-camu plants. It was conducted with the use of a randomized block experimental design with 5 treatments: 0; 40; 80; 120 and 160 kg ha-1 of N, eight replicates and seven plants per experimental parcel. The experiment lasted for a period of 270 days. The diameter of stem (mm) and the height of the plant (cm) were evaluated every 30 days and the number of branches and total length of branches (cm) were evaluated every 90 days. At the end of the experiment, chlorophyll a index, dry mass of the leaves (g), dry mass of the branches (g), dry mass of the roots (g), total dry mass (g), and the Dickson Quality Index (DQI) were evaluated. According to the results, camu-camu plants that did not receive nitrogen fertilization had a lower initial growth and the doses of N significantly influenced all parameters evaluated in the camu-camu plants, including parameters from a linear and a quadratic model. The dose of 123 kg ha-1 of N, applied via fertirrigation, produced better quality camu-camu plants. Furthermore, greater doses caused depressive effects on growth of camu-camu plants in the first year of cultivation in firm ground conditions and the indirect measurement of chlorophyll a index in camu-camu plants was suitable for the assessment of nutritional status in relation to N.